ADVERSE EFFECTS OF HYDROXYCHLOROQUINE (PLAQUENIL) IN THE TREATMENT OF RHEUMATOID ARTHRITIS (Лучшие интеллектуальные исследования, 2025)
Abstract: Hydroxychloroquine (Plaquenil) is an antimalarial drug commonly used in the management of autoimmune diseases such as rheumatoid arthritis (RA). While generally considered safe and well-tolerated, hydroxychloroquine is associated with a range of adverse effects, some of which can be serious. This article reviews the common and rare side effects of hydroxychloroquine when used in the treatment of RA, along with mechanisms, risk factors, and clinical implications.